Trefftz type approximation and the generalized finite element method - history and development - Zienkiewicz, Olgierd C. (Computer Assisted Methods in Engineering and Science; Vol 4 No 3-4 (1997), 2023)
This paper shows the essential unity between the known approximation procedures to differential equations. The boundary type approximations associated with Trefftz are shown to be a particular form of the weighted residual approximation and can provide a very useful basis for generating hybrid 'finite elements'. These can be used in combination with other finite element approaches.